Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan PD. Panca Motor - Kartika Septiary Pratiwi Musa (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2026)
This study aims to determine how much influence motivation and work environment have on employee performance at PD. Panca Motor Palembang. The object of the study was all employees of PD. Panca Motor Palembang who are engaged in the sale of Yamaha motorcycles. The type of research used was associative research with multiple linear regression analysis method using SPSS version 26. The population was 84 employees and a sample of 70 respondents was determined by the Slovin formula at a 5% error rate using the proportionate stratified random sampling technique. The results of the F test showed that motivation and work environment simultaneously had a positive and significant effect on employee performance at PD Panca Motor Palembang. The results of the partial t test showed that: 1) motivation had a positive and significant effect on employee performance at PD Panca Motor Palembang and 2) the work environment also had a positive and significant effect on employee performance at PD Panca Motor Palembang. The results of the coefficient of determination showed that 69.3% of most changes in employee performance could be explained by motivation and work environment, while the remaining 30.7% were influenced by other variables not included in this study.